Hunter territoriality creates refuges for threatened primates. (3rd June 2023) - Griffiths, Brian M; Bowler, Mark; Gilmore, Michael P
Summary: Unsustainable hunting threatens biodiversity in the tropics through the removal of key seed-dispersing frugivorous primates. Traditionally, hunting in the Amazon Basin was managed through hunter territoriality, with the threat of social sanctions for overexploitation. We examined hunter territoriality and differential prey selection as alternative hypotheses to central-place foraging. Territoriality occurred beyond common hunting grounds, which were on major rivers and immediately surrounding the community. Hunters displayed selectivity in prey choice, with 50% of hunters not hunting primates. The combination of hunter territoriality and differential prey selection means that over 22% of the hunted area of the Sucusari river basin could be considered primate refuge. Of the remaining hunted area, 16% was hunted relatively little by primate hunters. We suggest that the combination of territoriality and selection against primates creates refuges, mitigating the effects of sustained hunting pressure and contributing to the conservation of these species.